Decoupling water environment pressures from economic growth in the Yangtze River Economic Belt, China - Yuying Zhang (Elsevier, 2021)
China's economic development is gradually transforming from an extensive expansion mode to a green development mode that pursues environmental quality and environmental benefits. To achieve economic growth and reduce environmental pollution at the same time is the essence of decoupling. This paper combines the Tapio decoupling model and the Stochastic Impacts by Regression on Population, Affluence, and Technology (STIRPAT) model to analyze the decoupling performance and driving factors of economic output and water environment pressure of provinces and cities in the Yangtze River Economic Belt from 2004 to 2018. The results show that the overall water environment pressure and economic growth of the Yangtze River Economic Belt have shown a positive trend (from weak decoupling to strong decoupling). Strong decoupling areas were identified in the upper reaches of the Yangtze River (Sichuan, Guizhou, Yunnan, and Chongqing), the middle reaches of the Yangtze River (Jiangxi, Hubei, and Hunan), and the lower reaches (Shanghai, Jiangsu, Zhejiang, and Anhui). When compared with decoupling in the middle and lower reaches, the decoupling state of the upper reaches is unstable and tends to deteriorate. The driving factors of water environment pressure indicate that population size and urbanization are the main factors influencing wastewater discharge. The direction and size of the industrial structures are affected by policies and markets. Then, economic growth, fixed asset investment, and trade openness have had a positive impact on wastewater discharge. Technological progress and environmental regulations are important factors in controlling wastewater discharge. However, their current effect on wastewater discharge is not ideal. Therefore, while controlling the reasonable flow of population, each region should carry out industrial optimization and technological upgrading, and increase the management, capital, and technical support for the underdeveloped provinces of the Yangtze Economic Belt. This is necessary to achieve green economic development.